The effect of a weekly flywheel resistance training session on elite U-16 soccer players` physical performance during the competitive season. A randomized controlled trial - Raya-González, J.; Castillo, D.; de Keijzer, K. L.; Beato, M. (Research in Sports Medicine, 2021)
This study investigated the effects of a weekly flywheel resistance training session over a 10-week period on U16 soccer players` physical performance with special attention to change of direction ability (e.g., deficit [CODdef]). Twenty elite young soccer players were assigned to an experimental (EG, n = 10) or control (CG, n = 10) group. Unilateral countermovement jumps with dominant (CMJd) and non-dominant (CMJnd) leg, 10, 20, and 30-m linear sprint test and change of direction sprint test in 5 + 5 (COD10) and 10 + 10 m (COD20) were performed before and after flywheel training period. Significant within-group differences were found in CG in COD10 (p = 0.01; effect size [ES] = large) and CODdef10 (p = 0.03; ES = small) with dominant leg, while differences in EG were observed in CMJ (p = 0.001-0.01; ES = moderate-large) and in all COD and CODdef variables (p = 0.001-0.04; ES = large). Between-groups analysis revealed differences in favour of the EG in CMJ (p = 0.03-0.05) and COD and CODdef variables (p = 0.001-0.05). These findings suggest a weekly flywheel training session is suitable for improving jumping and COD abilities in U16 elite soccer players in season.